The Effect Of Geometrically Corrected Landsat Tm Data On The Accuracy Of The Landuse Classification Results : A Case Study in Semarang Municipality and Its Vicinity - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRACT This research was aimed at first, studying and comparing between the accuracies of the geometrically and non-geometrically corrected digital. Landsat data